2021
DOI: 10.3390/ijms22136882
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exogenous Application of Quercetin Derivative Solutions on the Course of Physiological and Biochemical Processes in Wheat Seedlings

Abstract: Quercetin, classified as a flavonoid, is a strong antioxidant that plays a significant role in the regulation of physiological processes in plants, which is particularly important in the case of biotic and abiotic stresses. The study investigated the effect of the use of potassium quercetin solutions in various concentrations (0.5%, 1.0%, 3.0% and 5.0%) on the physiological and biochemical properties of wheat seedlings. A pot experiment was carried out in order to determine the most beneficial dose of this fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…These metabolites include, in particular, phenolic compounds produced by the shikimate-phenylpropanoid biosynthetic pathway, which include quercetin [ 26 ]. In previous studies conducted by Jańczak-Pieniążek et al [ 39 ] and Migut et al [ 58 ], as a result of spraying with quercetin derivative (potassium quercetin complex), a positive, proportional to the concentrations used, effect of this flavonoid was demonstrated. This resulted in an improvement in the values of content of chlorophyll and selected parameters of chlorophyll fluorescence and gas exchange.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These metabolites include, in particular, phenolic compounds produced by the shikimate-phenylpropanoid biosynthetic pathway, which include quercetin [ 26 ]. In previous studies conducted by Jańczak-Pieniążek et al [ 39 ] and Migut et al [ 58 ], as a result of spraying with quercetin derivative (potassium quercetin complex), a positive, proportional to the concentrations used, effect of this flavonoid was demonstrated. This resulted in an improvement in the values of content of chlorophyll and selected parameters of chlorophyll fluorescence and gas exchange.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is still little information on the effect of exogenous quercetin on the functioning of plants exposed to stress, including salt stress [ 38 ]. Previous studies on wheat seedlings sprayed with various concentrations of quercetin derivative showed the stimulating role of this flavonoid on physiological and biochemical processes [ 39 ], which allowed the use of this agent in studies on plants under salt stress. The aim of the research was to show the effect of the exogenous application of solutions of the Q-Cu (II), characterised by high antioxidant activity, on wheat seedlings growing under saline conditions, and in particular to assess the efficiency of the photosynthetic apparatus and its antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the high efficiency in ROS elimination of quercetin rendered plants with prevalent protection against intense UVB radiation, heavy metal, osmotic stress, microbial infection, etc. Moreover, quercetin could induce phytohormone signaling pathways, including auxin (IAA) and abscisic acid (ABA), and regulate the activity of enzymatic and non-enzymatic antioxidants in a dose-dependent manner ( Jańczak-Pienia̧żek et al, 2021 ; Singh et al, 2021 ). On the other hand, rutin was documented to be a plant defense compound against cold stress ( Reimer et al, 2022 ), salinity ( Lim et al, 2012 ), and accumulated after UVB radiation ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, for instance, is a potent flavonoid with a diverse set of functions in plants [225]. Preliminary pot experiments suggest its potential as biofertilizer: spray inoculation of quercetin on wheat leaves increased physiological parameters related to chlorophyll content and fluorescence, and induced the accumulation of phenolics that are correlated with increased resistance to abiotic stress in a dose-dependent manner [296]. Seed priming with quercetin alleviated chromium toxicity in Trigonella seedlings, enhancing flavonoids accumulation in plant tissues, potentially quenching ROS induced by the metal contamination [297].…”
Section: Discussionmentioning
confidence: 99%